Avant-garde architecture: a view through the prism of the memory phenomenon - Fedoseeva Darya V. (Архитектон, 2024)
The article investigates the interaction between the memory phenomenon and avant-garde architecture by reviewing international and Soviet examples of how memory worked in the 1920-30s architecture, reminiscences of the avant-garde in the 20th-21st century architecture, and the latest inclusions of modernist and avant-garde architecture in current memory. Today, the avant-garde architecture occupies a place in the history of architecture not simply as a practice of denying the past and pursuing innovation, but as an era of fascination with great ideas based on a strong cultural foundation that made it possible to dream of the future. The avant-garde era played a great role in the formation of the entire architecture of the Modern Movement, and definition of the values and paradigms of modernity. The contemporary architectural avant-garde of the 21st century, for which one of the main tasks is the reception and translation of memory, serves as an embodiment of search for harmonious interaction between the past and the present. Examples are considered and conclusions are drawn about the nature of the interaction between avant-garde architecture and the phenomenon of memory.